Anomalous Values of Gravity and Magnetism in the Western Margin of Gondwana - Weidmann, María Cecilia (2015)
This research is based on a joint geological and geophysical study performed in the South Central Andes region. We acquired and processed terrestrial and satellite gravity data, as well as terrestrial and aeromagnetic data. Balanced geological cross-sections were constrained by physical properties of rocks (densities and magnetic susceptibilities obtained from field samples and well log). This study was performed in order to interpret a complex region that is still under debate: the location of Famatinian magmatic arc and its boundary with the Cuyania terrain. By means of gravity anomaly we developed direct and inverse models constrained by field data. The existence of a major high-density geological structure was evidenced from these models, located below the Vinchina basin and to the east of Cerro Rajado respectively. The existence of such gravity high could be linked to the boundary between the Famatinian magmatic arc and the accreted Cuyania wedge.